The Impact of Shipmaster Leadership Style and Ship Logistics Management on Ship Crews Performance: Implications For Tanker Ship Operational Performance - Suharto Abdul Majid; Endri Endri; Maman Zakaria; Edhie Budi Setiawan; Karnawi Kamar; Yosi Pahala (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
The research aims to identify the influence of the shipmaster leadership style and logistics management on the operational performance of tanker ships, which is mediated by the performance of the Ship's Crew. The research used a sample of 30 tanker and ship crew members at the Indonesian national shipping company PT. Waruna Nusa Sentana. The data analysis method applies a path analysis model to test direct and indirect effects. The research results show that leadership style, logistics management, and crew performance partially influence Ship operational performance. Leadership style and logistics management are also proven to influence crew performance directly. The captain's leadership style and logistics management indirectly affect the Ship's operational performance through the performance of the Ship's Crew. Overall, the operating performance of tankers at the shipping company PT. Waruna Nusa Sentana is influenced by the captain's leadership style, ship logistics management, and crew performance, both directly and indirectly. Keywords: shipmaster leadership style, ship logistics management, ship crews performance, tanker ship operational performance